Analogical thinking modifiability and math processing strategy - Tzuriel, David (Frontiers in Psychology, 2024)
Author (2022). Construction versus closed analogies: Effects of mediation and relation to working memory. Formazione Insegnamento -European Journal of Research on Education and Teaching.Author (2024). The effects of intervention with spatial analogies and working memory on math processing strategies. Unpublished paper. Talpiot Academic College.Author & George, T. ( 2009). Improvement of analogical reasoning and academic achievement by the Analogical Reasoning Programme (ARP). Educational and Child Psychology, 26, 71-94.Author & Klein, P.S. (1985). Analogical thinking modifiability in disadvantaged, regular, special education, and mentally retarded children.